Exploring the potential of highly efficient graphite/chitosan–PVC composite electrodes in the electrochemical degradation of Reactive Red 4 - Lahuri, Azizul Hakim (Wiley, 2021)
BACKGROUND Previous reported studies revealed that composite electrodes are effective and suitable for wastewater treatment applications owing to their high porosity and increased electrochemical active area. However, the critical challenges to the wider adoption of composite electrodes for environmental applications are the need to reduce the cost of electrode materials, and to improve both their long-term stability and electrocatalytic performance. This study aims to investigate the efficiency and stability of low-cost graphite/chitosan-polyvinyl chloride (C/Chi-PVC) composite electrodes for Reactive Red 4 (RR4) degradation. Toxicity of the treated RR4 wastewater also was investigated using a seed germination test.